O jeziku Pariškoga zbornika Code slave 73 (na tekstu psaltira i kantika) - Šimić, Marinka (2018)
U radu se analiziraju grafijske i fonološke osobitosti Pariškoga zbornika (Code slave 73) na temelju teksta psaltira i kantika te istražuje koliko su u njemu potvrđene značajke modruškoga govora, jer je, prema kolofonu, pisar Grgur Borislavić bio iz Modruša, kao i to u kojoj je mjeri očuvan stariji, tj. crkvenoslavenski jezični sloj. Opis ovoga rukopisa mogao bi pridonijeti boljem poznavanju modruškoga govora 14. stoljeća. Osvrnut ću se i na činjenicu da je rukopis pisan za prizidnice (redovnice) crkve sv. Julijana u Šibeniku te time mogući utjecaj namjene teksta na jezičnu koncepciju.
In this paper we analyze the graphic and the linguistic characteristics of the 1375 Paris Miscellany (Slave 73) by examining the Psalter and the canticles. Since the author of this oldest Croato-Glagolitic miscellany, Grgur Borislavić, was from Modruš, we have studied to what extent the language of the manuscript was influenced by the Modruš vernacular. Furthermore, considering that, according to the colophons, the target audience of the manuscript were the Šibenik nuns of St Julian’s Church we have also examined to what extent the linguistic concept was affected by the intended readership of the text. Linguistic research has proven that the text was written in the Croatian Old Slavonic language with some features of the Modruš vernacular, i.e. Čakavian. It is possible that some of these linguistic features were common to both the author and the inhabitants of Šibenik. The only linguistic characteristics that indicate that the text was adapted to the readership (Šibenik nuns) are the occasional Ikavisms. The Paris Miscellany is without a peer among the Croato-Glagolitic manuscripts. Not only is it the oldest complete miscellany, but it is also the only Glagolitic codex associated with Šibenik and one of the rare miscellanies that contain Biblical texts. Both the liturgical and the textological elements confirm the uniqueness of this manuscript...
Bibliografske bilješke uz tekst ; bibliografija: str. 180-184.
Sažetak ; Summary.
Keywords: Hrvatskoglagoljski zbornici -- Hrvatsko-staroslavenski jezik -- Modruški govor -- Čakavski dijalekt -- Psaltiri -- Šibensko glagoljaštvo